Pelatihan dan Pemanfaatan Teknologi Whatsapp Business Dalam Mengembangkan Penjualan Produk Pada UMKM - Eko Setia Budi; Ade Priyatna; Eva Zuraidah; Sanwani; Dito Tri Ardana; Aprilia Dimas Sahid; Ghifary Rafy Pratama; Kenji Ferdian Santosa; Muhamad Irfan (Forum Kerjasama Pendidikan Tinggi, 2024)
UMKM Tajur Halang Makmur is a social organization as a forum and means of developing every member of society who grows and develops on the basis of awareness and social responsibility from and for the community in the region, especially those engaged in medium and small businesses. Meanwhile, the membership of Jakarta MSMEs, hereinafter referred to as PKK Mothers, is every member of the community. Tajur Halang Makmur UKM Cooperative, Founded on 03 September 2019, address Ruko Ning's Residence Jalan Raya Kalisuren, Kalisuren Village, Tajurhalang District, Bogor Regency, Deed of establishment of the cooperative